Assessment of microarchitecture and crystal structure of hydroxyapatite in osteoporosis - Noor, Zairin; Sumitro, Sutiman B; Hidayat, Mohammad; Rahim, Agus Hadian; Taufiq, Ahmad (Universa Medicina, 2011)
Osteoporosis is characterized by lower bone mineral density (BMD) and microarchitectural degeneration, which tends to increase bone fragility and fracture risk. Bone microstructure depends on interactions between the mineral atoms, which may perform substitution or incorporation into bone crystals, and may dynamically take over the function of calcium or may become a complementary part. The mineral atoms may also become a composite in the hydroxyapatite crystals. The aim of this study was to find an association between the bone microstructure and hydoxyapatite crystal structure in osteoporosis, in comparison to normal bone. The subjects of this study were surgery patients at the Department of Orthopedics of Ulin General Hospital in Banjarmasin and other centers. Inclusion criteria consisted of the presence of fracture of trabecular bone, normal or osteoporotic BMD values, and no past history of chronic disease. Bone was obtained from fracture patients during surgery. The characteristics of the hydroxyapatite crystals were analyzed by X-ray diffraction (XRD) and the microarchitecture by scanning electron microscopy (SEM). SEM showed degeneration of the microarchitecture of osteoporotic bone, in comparison with normal bone. On XRD there was a peak of hydoxyapatite crystals only and no other crystal phases. Diffraction patterns showed a larger crystal size in osteoporotic bone as compared to normal bone, indicating higher porosity. It may be concluded that there is a difference in crystal size and morphologic distribution of hydoxyapatite in osteoporotic bone, determining bone microarchitecture.